(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
أكدت الدراسـة التصنيفيـة للجنس Plantago في محافظـة اللاذقيـة على وجود نوعين هما : Plantago coronopusL. وL. Plantago lagopus، وتـم تسجيـل تحت النوعين : Plantago major subsp Major وPlantago major subsp Intermedia لأول مرة إذ لم تشر أي من الدراسات السابقة إلى وجودهما في الفلورا السورية . تم التأكيد على وجود صنفين (lanceolatum var lanceolatum (communis Schlecht. Plantago وPlantago lanceolatum var dubia(L.) Lilij. ينتميان لهذا الجنس، وتم التمييز بين الأنواع بالاعتماد على الصفات المورفولوجية للأوراق، النورات ، الأزهار،المآبر،الثمار، البذور، وتمييز تحت النوعين بالاعتماد على الأوراق والبذور و طريقة تفتح الثمرة، بينما تم تمييز الصنفين بالاعتماد على الأوراق والأزهار، وعمق الأثلام لحامل النورة . أوضحت دراسة حبات الطلع في الأنواع المدروسة أنها كروية الشكل وذات ثقوب إنتاش عدة(3-14) ثقب، ومتوسط قطر حبة الطلع بلغ حوالي 22,4 ميكرون. The classification study for plantago genus in Lattakia emphasized that there are two kinds plantago coronopus L. and plantago lagopus L. Two under types plantago major subsp Intermedia and plantago major subsp Major, have been recorded for the first time as no previous studies have ever referred to their existence in Syria. It has also been emphasized that there are two categories that belong to this species: plantago lanceolatum var lanceolatum (communis Schlecht) and plantago lanceolatum var dubia(L)Lilij. A differentiation has been made between these kinds according to the morphological features of leaves, blossoms, flowers, anthers, fruits and seeds. The under types have been differentiated depending on leaves, seeds, and fruit. The two classifications have been differentiated depending on the leaves, flowers and the notch depth of the blossoms trestle. The pollen study in the studied species clarified that they have globose shape and several holes (3-14), and the diameter of the pollen grain is about 22,4.